What patients really think about asthma guidelines: barriers to guideline implementation from the patients' perspective. Issue 1 (December 2017) - Lingner, H.; Burger, B.; Kardos, P.; Criée, C.; Worth, H.; Hummers-Pradier, E.
Abstract Background Treatment of asthma does not always comply with asthma guidelines (AG). This may be rooted in direct or indirect resistance on the doctors' and/or patients' side or be caused by the healthcare system. To assess whether patients' concepts and attitudes are really an implementation barrier for AG, we analysed the patients' perspective of a "good asthma therapy" and contrasted their wishes with current recommendations. Methods Using a qualitative exploratory design, topic centred focus group (FG) discussions were performed until theoretical saturation was reached. Inclusion criteria were an asthma diagnosis and age above 18. FG sessions were recorded audio-visually and analysed via a mapping technique and content analysis performed according to Mayring (supported by MAXQDA®). Participants' speech times and the proportion of time devoted to different themes were calculated using the Videograph System® and related to the content analysis. Results Thirteen men and 24 women aged between 20 and 77 from rural and urban areas attended five FG. Some patients had been recently diagnosed with asthma, others years previously or in childhood. The following topics were addressed: (a) concern about or rejection of therapy components, particularly corticosteroids, which sometimes resulted in autonomous uncommunicated medication changes, (b) lack of time or money for optimal treatment, (c) insufficient involvement in therapy choices and (d) a desire for greater empowerment, (e) suboptimal communication between healthcare professionals and (f) difficulties with recommendations conflicting with daily life. Primarily, (g) participants wanted more time with doctors to discuss difficulties and (h) all aspects of living with an impairing condition. Conclusions We identified some important patient driven barriers to implementing AG recommendations. In order to advance AG implementation and improve asthma treatment, the patients' perspective needs to be considered before drafting new versions of AG. These issues should be addressed at the planning stage. Trial registration DRKS00000562 (German Clinical Trials Registry).